(untitled) (Journal of Hama University, 2024)
The research aims to identify the obstacles to employing the virtual laboratory in teaching science from the point of view of teachers of the first cycle of basic education. Sciences) includes (30) sub-items, then verifying their validity and reliability, and applying them to (229) male and female teachers. The study showed the following results: - Obstacles to employing the virtual laboratory in teaching science from the point of view of teachers of the first cycle of basic education came to a large extent and on all axes. In the last place are the obstacles related to the science curriculum. - There are no statistically significant differences between the averages of teachers’ answers to the questionnaire according to the variables of academic qualification and years of experience. - There are statistically significant differences between the averages of the teachers’ answers to the questionnaire according to the experimental courses and in favor of the teachers who did not follow the training courses. The study concluded with a set of proposals, the most important of which are: conducting training courses for teachers in order to provide them with the skills of using and employing virtual laboratories in teaching science, and methods of training students to use it.